Kinerja Organisasi Publik dalam Pengelolaan Sampah pada Dinas Lingkungan Hidup Kota Gorontalo - Muhammad Firdan Tegela; Ismet Sulila; Rusli Isa (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to examine the performance of public organizations in waste management at the Environmental Agency of Gorontalo City using indicators of public organizational performance, namely productivity, service quality, responsiveness, responsibility, and accountability. This study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that the productivity aspect has been implemented, although it has not yet been optimal, as reflected in the amount of waste managed each year Therefore, improvements in facilities, additional personnel, and greater public discipline are required to achieve more effective and efficient waste management. The service quality aspect has not been adequately achieved, particularly regarding the availability of waste management facilities and infrastructure, as well as the optimization of cleanliness in anticipation of future increases in waste production. The responsiveness aspect is considered fairly good, with prompt, firm, and friendly responses to public complaints, although part of the responsibility for cleanliness has been delegated to the subdistrict and village levels. The responsibility aspect demonstrates compliance with policies such as the Gorontalo City Regional Regulation through waste management and cleanliness programs. The accountability aspect is considered fairly good, as evidenced by the implementation of waste-handling and reduction programs and employee performance evaluations, however, greater transparency in public performance reporting is still needed.